2008
DOI: 10.1093/cercor/bhn091
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptual and Functional Consequences of Parietal Top-Down Modulation on the Visual Cortex

Abstract: The posterior parietal cortex (PPC) has been proposed to play a critical role in exerting top-down influences on occipital visual areas. By inducing activity in the PPC (angular gyrus) using transcranial magnetic stimulation (TMS), and using the phosphene threshold as a measure of visual cortical excitability, we investigated the functional role of this region in modulating the activity of the visual cortex. When triple-pulses of TMS were applied over the PPC unilaterally, the intensity of stimulation required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 28 publications
(27 reference statements)
7
69
2
Order By: Relevance
“…For instance, a recent study adopted a similar trifocal condition in which TMS was applied concurrently over the left PPC, right PPC, and either left or right visual cortex (V1/V2). The results showed that the increased visual cortical excitability (measured by the percentage of phosphenes induced by TMS) that was observed with unilateral parietal TMS was abolished when TMS was applied over the PPC bilaterally, implying the activation of an inhibitory transcallosal pathway (Silvanto et al, 2009). Interestingly, no hemispheric asymmetry was found.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For instance, a recent study adopted a similar trifocal condition in which TMS was applied concurrently over the left PPC, right PPC, and either left or right visual cortex (V1/V2). The results showed that the increased visual cortical excitability (measured by the percentage of phosphenes induced by TMS) that was observed with unilateral parietal TMS was abolished when TMS was applied over the PPC bilaterally, implying the activation of an inhibitory transcallosal pathway (Silvanto et al, 2009). Interestingly, no hemispheric asymmetry was found.…”
Section: Discussionmentioning
confidence: 88%
“…Neglect occurs as a consequence of an unbalanced system following damage to one of the processors, resulting in a bias toward the ipsilesional hemispace (Kinsbourne, 1977(Kinsbourne, , 1993. Here, we used a trifocal transcranial magnetic stimulation (TMS) method to directly test the hypothesis that the asymmetry of visuospatial functions may be due to an imbalance of interhemispheric interactions between the two parietal cortices (Silvanto et al, 2009). We chose to stimulate a region of the PPC that lies close to the posterior part of the intraparietal sulcus (cIPS) within the inferior parietal lobule (IPL), given that this area is a crucial node of the frontoparietal networks involved in visuospatial attention and neglect (Bisiach et al, 1986;Bowen et al, 1999;Karnath et al, 2002;Mort et al, 2003;Shulman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Applying causal time series analysis to fMRI BOLD data has supported the argument for functional connectivity (e.g., Granger causality analysis) (Bressler et al, 2008), but only direct manipulation of a brain region can provide definitive evidence for a cause and effect relationship. Indeed, the efficacy of using TMS (including in combination with imaging techniques) to show causal influences of one brain region on another has been demonstrated recently where direct stimulation over the FEF and IPS has shown to modify excitability (Silvanto et al, 2006(Silvanto et al, , 2009 as well as the BOLD signal in visual cortex (Ruff et al, 2006(Ruff et al, , 2008. These previous investigations indicate the presence of neural connectivity that may implement the link between attention control areas and their potential effect over perceptual areas.…”
Section: Discussionmentioning
confidence: 94%
“…Previous research has shown that using conditioning pulses over distant areas such as the motion sensitive area MT (Pascual-Leone and Walsh 2001), parietal cortex (Silvanto et al 2009), or frontal eye fields (Silvanto et al 2006) can affect the propensity of a subsequent pulse over the occipital cortex to elicit phosphenes. Other research has reported remote effects of TMS outside of the visual cortex (Hampson and Hoffman 2010;Ruff et al 2009).…”
Section: Discussionmentioning
confidence: 99%